Effects of different radical distal gastrectomy on postoperative inflammatory response and nutritional status in patients with gastric cancer - Cheng, Xuefei; Wang, Chuandong; Liu, Yi; Zhang, Xiaojuan; Zhou, Liyuan; Lin, Zhizun; Zeng, Wei; Liu, Lihang; Yang, Changshun; Li, Weihua (Frontiers in Surgery, 2023)
Objectives: The inflammatory response caused by gastric cancer surgery and the low nutritional status of patients with gastric cancer can cause growth of tumour cells, reduce immunity, and increase tumour burden. We investigated the effects of different surgical methods on postoperative inflammatory response and nutritional status in patients with distal gastric cancer. Methods: Clinical data of 249 patients who underwent radical distal gastrectomy for distal gastric cancer from February 2014 to April 2017 were retrospectively analysed. Patients were divided according to the surgical method (open distal gastrectomy [ODG], laparoscopic-assisted distal gastrectomy [LADG] and total laparoscopic distal gastrectomy [TLDG]). Characteristics of different surgical procedures, including inflammation parameters and nutritional indicators, and different time points (preoperatively, 1 day postoperatively, and 1 week postoperatively) were compared using non-parametric test analysis. Results: At postoperative day 1, white blood cell count [WBC], neutrophil count [N], neutrophil/lymphocyte ratio [NLR], and platelet/lymphocyte ratio [PLR] increased in the three groups, and △N and △NLR were significant; the smallest change was observed in TLDG (P<0.05). Albumin [A]and prognostic nutrition index [PNI] significantly decreased; the smallest △A and △PNI, which were statistically significant, were noted in TLDG. One week postoperatively, WBC, N, NLR, and PLR decreased, and WBC, N, and NLR showed significant difference. Aand PNI of the three groups increased after 1 week, and A and PNI showed significant differences. Conclusion: Postoperative inflammatory response and nutritional status of patients with distal gastric cancer are associated with the surgical technique. TLDG has little influence on the inflammatory response and nutritional level compared with LADG and ODG.